2013
DOI: 10.1108/nfs-08-2011-0083
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of Brazilian children's habits

Abstract: Purpose-The purpose of this paper is to investigate television viewing habits of children from low-income families, their consumption of fruits, vegetables and snacks, as well as their spending habits. Design/methodology/approach-11 focus groups were conducted with 54 public school students aged seven to ten years, divided by sex and age. Transcription of the discussions was processed by content analysis. Family income was indirectly assessed through classification of parents' occupations. Findings-The habit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This finding was in line with previous studies of family well habituation. For example, controlling of parents on which television programs were watched by children would lead nutritional behaviour (Nascimento & Fiates, 2013). Moreover, young consumers' were less ability to implement such knowledge into the reality of their daily food behaviour (Brown, Mcilveen, & Strugnell, 2000) especially on urban household (Y1ld1r1m & Ceylan, 2008).…”
Section: Factors Affecting the Attitude Toward Halal Labelmentioning
confidence: 99%
“…This finding was in line with previous studies of family well habituation. For example, controlling of parents on which television programs were watched by children would lead nutritional behaviour (Nascimento & Fiates, 2013). Moreover, young consumers' were less ability to implement such knowledge into the reality of their daily food behaviour (Brown, Mcilveen, & Strugnell, 2000) especially on urban household (Y1ld1r1m & Ceylan, 2008).…”
Section: Factors Affecting the Attitude Toward Halal Labelmentioning
confidence: 99%
“…A private school was chosen because other studies conducted in the municipality had identified that children from private schools were more likely to consume ultra-processed foods 25 . The chosen age group was that of the analytical stage of consumer socialization, in which children are capable of making a weighted assessment about a theme, considering many attributes and analyzing the cost/benefit relationship 26 .…”
Section: E T H O D Smentioning
confidence: 99%